DYNAMIC SIMULATION AND COMPOSITION CONTROL IN A 10 L MIXING TANK - Yulius Deddy Hermawan; Gogot Haryono (Dept. of Chemical Engineering, Diponegoro University, 2012)
The open loop experiment of composition dynamic in a 10 L mixing tank has been successfully done inlaboratory. A 10 L tank was designed for mixing of water (as a stream-1) and salt solution (as astream-2 with salt concentration, c2 constant). An electric stirrer was employed to obtain uniformcomposition in tank. In order to keep the liquid volume constant, the system was designed overflow. Inthis work, 2 composition control configurations have been proposed; they are Alternative-1 andAlternative-2. For Alternative-1, the volumetric-rate of stream-1 was chosen as a manipulatedvariable, while the volumetric-rate of stream-2 was chosen as a manipulated variable for Alternative-2. The composition control parameters for both alternatives have been tuned experimentally. Thevolumetric-rate of manipulated variable was changed based on step function. The outlet stream’scomposition response (c3) to a change in the input volumetric-rate has been investigated. Thisexperiment gave Proportional Integral Derivative (PID) control parameters. The gain controllers Kc[cm6/(gr.sec)] for Alternative-1 and Alternative-2 are -34200 and 40459 respectively. Integral timeconstant ( tI) and Derivative time constant (tD) for both alternatives are the same, i.e. tI = 16 second,and tD = 4 second. Furthermore, closed loop dynamic simulation using computer programming wasalso done to evaluate the resulted tuning parameters. The developed mathematical model ofcomposition control system in a mixing tank was solved numerically. Such mathematical model wasrigorously examined in Scilab software environment. The results showed that closed loop responses inPID control were faster than those in P and PI controls.